Distributed systems : concurrency and consistency - Perrin, Matthieu (Kidington, Oxford, UK : Elsevier, 2017)
Distributed Systems: Concurrency and Consistency explores the gray area of distributed systems and draws a map of weak consistency criteria, identifying several families and demonstrating how these may be implemented into a programming language. Unlike their sequential counterparts, distributed systems are much more difficult to design, and are therefore prone to problems. On a large scale, usability reminiscent of sequential consistency, which would provide the same global view to all users, is very expensive or impossible to achieve. This book investigates the best ways to specify the objects that are still possible to implement in these systems.
Includes bibliographical references and index.
Vendor-supplied metadata.
Keywords: Electronic data processing -- Distributed processing; COMPUTERS / Computer Literacy; COMPUTERS / Computer Science; COMPUTERS / Data Processing; COMPUTERS / Hardware / General; COMPUTERS / Information Technology; COMPUTERS / Machine Theory; COMPUTERS / Reference; Electronic data processing -- Distributed processing; Electronic books